The Ecological Thought: Timothy Morton: El pensamiento ecológico (trad. Fernando Borrajo). Barcelona: Paidós, 2018. 205 pp. - Gómez S´ánchez, Ruth; Español; Español, Inglés; Español (Analysis. Journal of Philosophical Research, 2020)
Book Review of the Spanish translation of Timothy Morton's The ecological Thought"Ecology means less nature and more awareness." Such would be the proposal of the philosopher Timothy Morton (London, 1968) in this work. Ecological thinking is an eclectic essay where we are presented with an ecological way of thinking, which has less to do with science than with the humanities. The key to ecological thinking according to Morton is precisely this: its ramification and diversity. It starts from the consideration that all beings are connected to each other in a "mesh"; as nothing exists by itself, nothing is fully "itself". What we contemplate is an immensity of infinitesimal differences, which will require us to "think big" (that's the title of chapter 1 of the book). In the hand of art, philosophy, literature, music and popular culture, the author tries to trace in three chapters a new ecological aesthetic: dark ecology, a notion that gives title to a previous work of Morton in 2018, a thought capable of expressing the irony and uncertainty in which we locate the Mortonian ecology.